A PPAR-gamma agonist attenuates pulmonary injury induced by irradiation in a murine model. Issue 3 (December 2015) - Mangoni, Monica; Sottili, Mariangela; Gerini, Chiara; Bonomo, Pierluigi; Bottoncetti, Anna; Castiglione, Francesca; Franzese, Ciro; Cassani, Sara; Greto, Daniela; Masoni, Tatiana; Meattini, Icro; Pallotta, Stefania; et al.
Highlights: Radiotherapy leads to side effects because it affects normal tissues near the target. Thoracic radiotherapy can cause radiation pneumonitis and pulmonary fibrosis. Rosiglitazone has anti-inflammatory, antifibrotic and antineoplastic properties. Rosiglitazone reduced signs of radiation-induced lung toxicity in a mouse model. Rosiglitazone could be proposed as a radioprotective agent in thorax irradiation. Abstract: Purpose/objective(s): Due to its anti-inflammatory, antifibrotic and antineoplastic properties, the PPAR-γ agonist rosiglitazone is of interest in the prevention and therapy of radiation-induced pulmonary injury. We evaluated the radioprotective effects of rosiglitazone in a murine model of pulmonary damage to determine whether radioprotection was selective for normal and tumor tissues. Methods: Lungs in C57BL/6J mice were irradiated (19 Gy) with or without rosiglitazone (RGZ, 5 mg/kg/day for 16 weeks, oral gavage). Computed tomography (CT) was performed and Hounsfield Units (HU) were determined during the observation period. Histological analysis and evaluation of fibrosis/inflammatory markers by western blot were performed at 16 weeks. A549 tumor-bearing CD1 mice were irradiated (16 Gy) with or without RGZ, and tumor volumes were measured at 35 days. Results: Rosiglitazone reduced radiologic and histologic signs of fibrosis, inflammatory infiltrate, alterations to alveolar structures, and HU lung density that was increased due to irradiation. RGZ treatment also significantly decreased Col1, NF-kB and TGF-β expression and increased Bcl-2 protein expression compared to the irradiation group and reduced A549 clonogenic survival and xenograft tumor growth. Conclusions: Rosiglitazone exerted a protective effect on normal tissues in radiation-induced pulmonary injury, while irradiated lung cancer cells were not protected in vivo and in vitro. Thus, rosiglitazone could be proposed as a radioprotective agent in the treatment of lung cancer.